A Facile Method to Enhance Photovoltaic Performance of Benzodithiophene‐Isoindigo Polymers by Inserting Bithiophene Spacer. Issue 6 (18th November 2013) - Ma, Zaifei; Dang, Dongfeng; Tang, Zheng; Gedefaw, Desta; Bergqvist, Jonas; Zhu, Weiguo; Mammo, Wendimagegn; Andersson, Mats R.; Inganäs, Olle; Zhang, Fengling; Wang, Ergang
<x xml:space="preserve">Abstract</x> A series of conjugated polymers containing benzodithiophene as donor and isoindigo as acceptor with no, one, two and three thiophene spacer groups is synthesized and characterized. The polymer with bithiophene as a spacer has a superior efficiency of 7.31% in solar cells. This demonstrates an important design strategy to produce polymers for high‐performance solar cells by inserting thiophene spacer groups. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>